Ferrierite zeolite passivation and its catalytic application in toluene disproportionation. (23rd November 2019) - Mesa, S.; Arboleda, J.; Echavarría, A.; López-Suárez, F.E.
Highlights: Ferrite zeolite has particular structure bidimensional channel system. Synthesis, characterization and passivation method by chemical liquid deposition. Affecting the acid properties of parent zeolite. Shape-selective performance in the production of p-xylene. Toluene disproportionation reaction. Abstract: Ferrierite zeolites have been prepared, characterized and evaluated in toluene disproportionation. The materials were synthesized using a hydrothermal method. A passivation process (chemical liquid deposition, CLD) was applied in order to modify the acidic properties of parent zeolite and the shape-selective performance in the production of p-xylene by the disproportionation of toluene. The catalyst structures and chemical compositions were characterized by SEM, XRD, XRF, TGA, DTA, nitrogen adsorption/desorption, and NH3 -TPD measurements. Textural properties and acidity of ferrierite zeolites were changed by the passivation procedure. The strength and amount of acid sites on the materials diminished with increasing the modification cycles in the passivation process. In toluene disproportionation, the passivated materials were substantially more para-selective (56% at 648 K and 689.5 KPa) than the parent zeolite (H-form). Overall, the temperature and pressure ranges evaluated were from 689.5 to 2757.9 KPa and 648–698 K.